Vault prolapse - a decade’s experience - Jois, Srinivas Krishna; Rao, Lavanya Gurumurthy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vault prolapse although an uncommon condition is an annoying problem to the patient often requiring repeat surgery for relief. The objective of this study was to study the clinical parameters of patients of vault prolapse, predisposing factors, pre-op and post-op symptoms, treatment provided and outcomes of the same over ten years at Vani Vilas Hospital, Bangalore Medical College. Methods: A retrospective study was conducted on all patients admitted with vault prolapse and treated for the same from 2005 to 2014. Data was collected and analyzed. Results: commonest symptom associated was mass per vagina with difficulty in voiding urine (80%). Straining at stools and sexual dysfunction was seen in fewer than 30%. 64% of our patients had TAH and the mean duration before symptoms was 12 years (11.7 years). Majority of our patients underwent sacrospious fixation (42%) while 24% underwent traditional repair. Abdominal sacrocolpopexy was performed on 8 patients. Intra-op complications of haemorrhage seen in 1, ureteric injury in 2 and injury to rectum in 1 patient. ICU admission was required for 5. 80% 0f the patients were available for follow up at 2 weeks and 6 weeks and >90% expressed subjective improvement in symptoms. Only one underwent re operation at 3 months for failure. Conclusions: Vault prolapse is not an uncommon condition following hysterectomy especially if it was done at a young age. Careful selection of patients, measures to prevent this condition during primary hysterectomy is the need of the hour.